The Zircon U-Pb Age, Hf Isotopes, and Lithogeochemistry of Ore-Bearing Rocks from the Archean Hongtoushan Volcanogenic Massive Sulfide Deposit in the North China Craton: Implications for Tectonic Setting - You, Xinwei; Wang, Ende; Men, Yekai; Fu, Jianfei; Song, Kun; Ma, Sishun (Minerals (Basel), 2024)
Volcanogenic massive sulfide (VMS) deposits are globally significant sources of metals. The Hongtoushan VMS deposit is the only large Archean Cu-Zn VMS deposit in the North China Craton, carrying substantial economic value. Significant deformation and metamorphism have made the tectonic setting of the Hongtoushan VMS deposit the subject of extensive debate. This study investigates the petrogenesis and chronology of the ore-bearing host rocks from the Hongtoushan Cu-Zn VMS deposit in the North China Craton. By utilizing whole-rock geochemical analyses and zircon dating, this research sheds light on the origin and evolution of the ore-bearing rocks within the deposit. The whole-rock geochemical analysis data indicate that the Hongtoushan ore-bearing rock series is mainly composed of amphibole plagioclase gneiss (basalt protolith) and biotite plagioclase gneiss (andesite and rhyolite protolith), suggesting a complete volcanic cycle from basic to medium-acidic volcanic rocks. The amphibole plagioclase gneiss has slight LREE enrichment patterns with unremarkable depletions of Nb, Ta, and Ti and belongs to contaminated ocean plateau basalt (OPB) in terms of composition, which is generally interpreted as being generated from the mantle plume head. Meanwhile, the biotite plagioclase gneiss has relatively steep LREE enrichment distribution patterns with remarkable negative Ta, Nb, and Ti anomalies and a wide range of Zr/Y ratios, indicating their classification as FI- and FII-type felsic rocks; they were likely formed through the fractional crystallization of basic magma combined with crustal assimilation. When combined with the zircon dating results, the ore-bearing host rocks of the Hongtoushan VMS deposit were generated via a continuous magmatic evolution process. The zircon dating of the host rocks indicates a formation age of between 2609 and 2503 Ma, with metamorphic events between 2540 and 2466 Ma, which is consistent with the 2.5 Ga-related global mantle plume event. Further research shows that the ore-bearing host rocks are more likely to have been formed in a mantle plume-related stretching environment, possibly a margin rift.